The Impact of High-Involvement Human Resources Practices on Innovative Work Behavior: The Mediating Role of Employee Engagement - Abd elhamed, Abeer Abass (The Arab Journal of Administration, 2025)
Drawing on principles of social exchange theory, Ability-Motivation-Opportunity model, and resource based- view, this research aims to examine the impact of high-involvement human resources practices (Recognition; Empowerment; Competence development, Fair rewards; Information sharing) on innovative work behavior, and investigate the mediating role of employee engagement in the relationship between HI-HR practices and employee’s innovative work behavior at the Egyptian telecommunications companies context. Accordingly, the research adopted a quantitative descriptive research design for the purpose of empirical test of hypotheses, measuring research variables by valid and reliable measurement items have been confirmed in relevant literatures. Questionnaire was designed to data collection from a quota sample of (250) employees at Egyptian four telecommunications companies (Vodafone, Orange, Etisalat, We). Data were coded and analyzed using structure equation modeling technique. The statistical analysis results showed that Egyptian ICT generally, and telecommunications specifically, companies have a high level of interest in employee innovative performance in light of global environmental conditions and COVID-19 pandemic, and seek hardly to enhance employees’ innovative work behaviors through adopting HI-HR practices and improving their engagement at work. Their evaluation means increased to (3.9). The results also, revealed that there is a significant positive effect of HI-HR practices on employees’ innovative behaviors at telecommunications companies, the most important influenced practices are competence development with standardized effect coefficient of (.38) and information sharing (.26). All variables explain (89%) of varience innovative behavior. In addition, the study results revealed that practices of recognition, empowerment and competence development are the most important predictors of enhancing employee engagement, and explain (55%) of varience in employee engagement. Also, results concluded that employee engagement have a significant mediating role in the relationship between HI-HR practices (recognition, development, information sharing) and innovative work behavior.